Experimental and numerical analysis on vibration features of typical external pipe in aero-engine. (29th June 2019) - Cheng, Guanbing; Wang, Xuan; Wang, Guoda
The aero-engine pipe vibration phenomenon is a serious complicated problem in engine structure design and application. In this paper, an experimental and computational study was implemented on the aviation straight and L-shape pipe vibration characteristics. The pipe vibration shape and natural frequency were obtained by both hammering and Finite Element Methods (FEM). Effects of fluid type, pressure and temperature were examined on pipe vibration characteristic parameters. The results show that the pipe vibrates along transverse and vertical directions. There are slight differences in pipe vibrating natural frequency in the two directions. The pipe experimentally natural frequency and vibration modes agree well with those obtained in FEM computation. The fluid type, pressure and temperature can change the pipe vibrating amplitude values, but cannot influence the pipe vibration modal characteristics. Varying fluid pressure and temperature can to some extent change the pipe natural frequencies.